Dimers, monomers and pentacoordination in a series of earth-abundant transition metal dibromido complexes supported by a neutral SNS ligand framework. (1st November 2018) - Hameed, Yasmeen; Ouanounou, Sarah; Jurca, Titel; Gabidullin, Bulat; Korobkov, Ilia; Richeson, Darrin
Graphical abstract: The first systematic application of bis(thioether)pyridine SNS ligands in coordination chemistry of first-row transition-metal bromides and the first structurally characterized SNS complexes of Mn and Fe are reported. Abstract: Pincer-type architectures represent an important class of ligand frameworks for the design and synthesis of transition metal coordination complexes and catalysts. The first systematic application of bis(thioether)pyridine "SNS" ligands in coordination chemistry of first-row transition-metal bromides and the first structurally characterized "SNS" complexes of Mn and Fe are reported. The complexes were characterized by single crystal X-ray analysis, UV–Vis and FTIR spectroscopy, mass-spectrometry, elemental analysis, and where appropriate by Evans method. Analysis of the resulting complexes reveals a set of monomeric and dinuclear species, whose coordination mode is associated with a delicate balance of structural features arising from the metal's d-orbital occupancy and the steric load of the ligand. Dimerization of the solid state structure appears to be primarily favored through lower steric load from the ligand and lower metal d-electron count.